An Inverse Shape‐Memory Hydrogel Scaffold Switching Upon Cooling in a Tissue‐Tolerated Temperature Range. Issue 6 (30th January 2022) - Tartivel, Lucile; Blocki, Anna M.; Braune, Steffen; Jung, Friedrich; Behl, Marc; Lendlein, Andreas
Abstract: Tissue reconstruction has an unmet need for soft active scaffolds that enable gentle loading with regeneration‐directing bioactive components by soaking up but also provide macroscopic dimensional stability. Here microporous hydrogels capable of an inverse shape‐memory effect (iSME) are described, which in contrast to classical shape‐memory polymers (SMPs) recover their permanent shape upon cooling. These hydrogels are designed as covalently photo cross‐linked polymer networks with oligo(ethylene glycol)‐oligo(propylene glycol)‐oligo(ethylene glycol) (OEG‐OPG‐OEG) segments. When heated after deformation, the OEG‐OPG‐OEG segments form micelles fixing the temporary shape. Upon cooling, the micelles dissociate again, the deformation is reversed and the permanent shape is obtained. Applicability of this iSME is demonstrated by the gentle loading of platelet‐rich plasma (PRP) without causing any platelet activation during this process. PRP is highly bioactive and is widely acknowledged for its regenerative effects. Hence, the microporous inverse shape‐memory hydrogel (iSMH) with a cooling induced pore‐size effect represents a promising candidate scaffold for tissue regeneration for potential usage in minimally invasive surgery applications. Abstract : This work presents microporous hydrogel scaffolds capable of a cooling‐induced inverse shape‐memory effect (iSME). In an iSME cooling reverses a deformation to the permanent shape. The iSME was based on partial micelle formation of an ABA triblock copolymer, acting as temporary cross‐links. Upon cooling micelles disintegrated, resulting in the recovery of the original shape of the scaffold.